Skin diseases are more common than we think: screening results of an unreferred population at the Munich Oktoberfest. (19th March 2019) - Tizek, L.; Schielein, M.C.; Seifert, F.; Biedermann, T.; Böhner, A.; Zink, A.
Abstract: Background: Skin diseases are ranked as the fourth most common cause of human illness, resulting in an enormous non‐fatal burden. Despite this, many affected people do not consult a physician. Accordingly, the actual skin disease burden might be even higher since reported prevalence rates are typically based on secondary data that exclude individuals who do not seek medical care. Objective: The aim of the study was to investigate the prevalence of skin diseases in an unreferred population in a real‐life setting. Methods: A cross‐sectional study of 9 days duration was performed in 2016 at the 'Bavarian Central Agricultural Festival', which is part of the Munich Oktoberfest. As part of a public health check‐up, screening examinations were performed randomly on participating visitors. All participants were 18 years or older and provided written informed consent. Results: A total of 2701 individuals (53.5% women, 46.2% men; mean age 51.9 ± 15.3 years) participated in the study. At least one skin abnormality was observed in 1662 of the participants (64.5%). The most common diagnoses were actinic keratosis (26.6%), rosacea (25.5%) and eczema (11.7%). Skin diseases increased with age and were more frequent in men (72.3%) than in women (58.0%). Clinical examinations showed that nearly two‐thirds of the affected participants were unaware of their abnormal skin findings. Conclusion: Skin diseases might be more common than previously estimated based on the secondary data of some sub‐populations. Further information and awareness campaigns are needed to improve people's knowledge and reduce the global burden associated with skin diseases.